Preparation, characterization, and removal of nitrate from water using vacant polyoxometalate/TiO2 composites - Wang, Lingsheng (Environmental technology, 2023)
Due to the rapid development of industry and agriculture, nitrate pollution in groundwater has been continuously increasing. NO3-N is a chemically stable nitrogen species and is quite difficult to remove. In this study, using heteropoly silicotungstate K8[α-SiW11O39] and Cu2+ as the active components, SiW11 and Cu2+ were loaded onto TiO2 by a sol-gel method to prepare a composite photocatalyst SiW11/TiO2/Cu. The photocatalytic reduction of dissolved NO3-N was subsequently performed using SiW11/TiO2/Cu under UV irradiation, and the influence of different experimental parameters on the photocatalytic performance was investigated. The mechanism of NO3-N reduction by the composite catalyst was also investigated. Free radicals existing within the system were detected by ESR spectroscopy, and the results indicated that CO2- anion free-radicals were generated by the reaction of photogenerated holes and formic acid (HCOOH). At a SiW11/TiO2/Cu dose of 1.2 g L-1 and in the presence of HCOOH as a hole scavenger, the proposed composite catalytically reduced NO3-N anddemonstrated significantadvantages in terms of its photocatalytic activity in comparison with pure TiO2. In particular, the removal efficiency of NO3-N and the selectivity of nitrogen achieved a maximum of 96% and 77%, respectively